Mindfulness-based interventions in the workplace: An inclusive systematic review and meta-analysis of their impact upon wellbeing. Issue 5 (3rd September 2019) - Lomas, Tim; Medina, Juan Carlos; Ivtzan, Itai; Rupprecht, Silke; Eiroa-Orosa, Francisco José
ABSTRACT: Given the demanding nature of many professions, efforts are ongoing to develop initiatives to improve occupational wellbeing, including mindfulness-based interventions (MBIs). To assess the efficacy of MBIs, meta-analytic procedures were conducted on 35 randomized controlled trials derived from an earlier inclusive systematic literature search (covering all occupations, MBIs, and wellbeing-related outcomes). Mindfulness had moderate effects on deficit-based outcomes such as stress ( SMD  = −0.57), anxiety ( SMD  = −0.57), distress ( SMD  = −0.56), depression ( SMD  = −0.48), and burnout ( SMD  = −0.36), and moderate to small effects on asset-based outcomes like health ( SMD  = 0.63), job performance ( SMD  = 0.43), compassion and empathy ( SMD  = 0.42), mindfulness ( SMD  = 0.39), and positive wellbeing ( SMD  = 0.36), while no effects were observed for emotional regulation. However, the quality of the studies was inconsistent, suggesting more high-quality randomised controlled trials are needed.